IS E-LEARNING MADRASAH CHALLENGING FOR TEACHERS? A CASE STUDY IN SOUTH SUMATERA - Avista, Della; Warna, Dewi; Riznanda, Winny Agustia (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2022)
ABSTRACT: E-Learning Madrasah is one of the web-based learning tools used by teachers in Madrasah due to its flexibility. However, preliminary study found that some teachers encountered challenges in using it. Thus, this study was aimed to investigate EFL teachers’ challenges on the use of E-Learning Madrasah in MAN 1 Pangkalan Balai, Banyuasin. One of the qualitative approach, case study design was applied with two teachers of English as the participants by using purposeful sampling. Semi-structured interviews were used and analyzed by using thematic analysis. This study revealed EFL teachers' challenges in using E-learning Madrasah, such as: (1) EFL teachers' capability in managing the web (E-learning Madrasah), (2) web management, (3) limited Connection, (4) technical issues, (5) pedagogical matters, and (6) lack of motivation in using web due to the school system. This study implied that more development on the web, internet connection, and training for teachers are required to be improved. Keywords: E-learning madrasah, teachers’ challenges